2020
DOI: 10.1088/1361-6528/abb84e
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond PLD-grown YF3 nanoparticle thin films as improved filterless VUV photoconductive detectors

Abstract: A photoconductive detector (PCD) responding only to vacuum ultraviolet (VUV) radiations below 180 nm without any filter was fabricated using an yttrium fluoride (YF3) thin film grown by femtosecond (fs) laser pulsed laser deposition (PLD). The structural morphology (particle size and surface roughness) of the thin film was improved using a low laser fluence and a high substrate temperature during the fabrication. The smallest average particle size achieved was 159 nm with a roughness of 37 nm at a laser fluenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, we also investigate the improvement of its photoconductivity in the VUV region using TiO 2 thin films deposited on high resistivity undoped silicon (Si), quartz glass (SiO 2 ), and soda lime glass (SLG) substrates with thicknesses of 80 nm, 500 nm, and 1000 nm. Our results show that TiO 2 thin films in general—but especially TiO 2 thin films deposited on SiO 2 substrate with a thickness of 80 nm exhibit higher photoconductivity, with photocurrents reaching the milli-Ampere range, compared with our previous works using wide band gap fluorine-based insulator thin film photoconductive detectors [ 26 , 27 ] and gamma-ray irradiated detectors, based on amorphous TiO 2 on SLG substrate [ 28 ]. The potential of using TiO 2 thin films as photoconductive detectors of VUV radiation will contribute to the enhancement of the many applications of this high energy radiation.…”
Section: Introductionmentioning
confidence: 48%
“…Furthermore, we also investigate the improvement of its photoconductivity in the VUV region using TiO 2 thin films deposited on high resistivity undoped silicon (Si), quartz glass (SiO 2 ), and soda lime glass (SLG) substrates with thicknesses of 80 nm, 500 nm, and 1000 nm. Our results show that TiO 2 thin films in general—but especially TiO 2 thin films deposited on SiO 2 substrate with a thickness of 80 nm exhibit higher photoconductivity, with photocurrents reaching the milli-Ampere range, compared with our previous works using wide band gap fluorine-based insulator thin film photoconductive detectors [ 26 , 27 ] and gamma-ray irradiated detectors, based on amorphous TiO 2 on SLG substrate [ 28 ]. The potential of using TiO 2 thin films as photoconductive detectors of VUV radiation will contribute to the enhancement of the many applications of this high energy radiation.…”
Section: Introductionmentioning
confidence: 48%
“…[32] We have previously demonstrated that fluoride crystals and thin films can be used as photoconductive detectors in the VUV region. [33][34][35][36][37] Their spectral response can be adjusted by controlling the respective composition ratios and optical quality. [33][34][35][36][37] Unlike silicon-based detectors developed by relatively mature production technologies and WBG semiconductor-based detectors, which are widely investigated in current literature, the development of fluoride photodetectors is in its infancy and thus not much is known regarding the correlation between fabrication parameters and photodetector performance.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] Their spectral response can be adjusted by controlling the respective composition ratios and optical quality. [33][34][35][36][37] Unlike silicon-based detectors developed by relatively mature production technologies and WBG semiconductor-based detectors, which are widely investigated in current literature, the development of fluoride photodetectors is in its infancy and thus not much is known regarding the correlation between fabrication parameters and photodetector performance. In this work, we investigated the influence of annealing on the interface between neodymium trifluoride (NdF 3 ) thin film and quartz (SiO 2 ) substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength detection limit of such detectors is dictated by the band gap of the semiconductor material, without having to use optical filters. Furthermore, the band gap can be tuned by controlling the composition ratio [ 14 ] and the fabrication parameters [ 15 , 16 ]. Zinc oxide (ZnO) [ 17 ], gallium nitride (GaN) [ 18 ], aluminum nitride (AlN) [ 19 , 20 ], and boron nitride (BN) [ 21 , 22 , 23 , 24 , 25 ] are semiconductor materials that have been reported as UV photoconductive detectors, each with their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%